Treatment-Based Classification System for Low Back Pain: Revision and Update. Issue 7 (1st July 2016) - Alrwaily, Muhammad; Timko, Michael; Schneider, Michael; Stevans, Joel; Bise, Christopher; Hariharan, Karthik; Delitto, Anthony
Abstract: The treatment-based classification (TBC) system for the treatment of patients with low back pain (LBP) has been in use by clinicians since 1995. This perspective article describes how the TBC was updated by maintaining its strengths, addressing its limitations, and incorporating recent research developments. The current update of the TBC has 2 levels of triage: (1) the level of the first-contact health care provider and (2) the level of the rehabilitation provider. At the level of first-contact health care provider, the purpose of the triage is to determine whether the patient is an appropriate candidate for rehabilitation, either by ruling out serious pathologies and serious comorbidities or by determining whether the patient is appropriate for self-care management. At the level of the rehabilitation provider, the purpose of the triage is to determine the most appropriate rehabilitation approach given the patient's clinical presentation. Three rehabilitation approaches are described. A symptom modulation approach is described for patients with a recent—new or recurrent—LBP episode that has caused significant symptomatic features. A movement control approach is described for patients with moderate pain and disability status. A function optimization approach is described for patients with low pain and disability status. This perspective article emphasizes that psychological and comorbid status should be assessed and addressed in each patient. This updated TBC is linked to the American Physical Therapy Association's clinical practice guidelines for low back pain.